Antimicrobial and Antibiofilm Activities of 4,5-Dihydro-1H-pyrazole-1-carboximidamide Hydrochloride against Salmonella spp. - Andressa C. Damim; Danilo Y. de Albuquerque; Fabiana G. S. Dantas; Fernanda Galvão; Melyssa Negri; Lucas Pizzuti; Gleison A. Casagrande; Sumbal Saba; Jamal Rafique; Kelly M. P. de Oliveira (Journal of Chemistry)
In the present study, the antimicrobial and antibiofilm activities of two 4,5-dihydro-1H-pyrazole-1-carboximidamide hydrochloride, (trifluoromethyl) phenyl-substituted (compound 1) and bromophenyl-substituted (compound 2), were evaluated against four Salmonella spp. serotypes through broth microdilution and biofilm-forming activity. Further, the cytotoxicity of the compounds was evaluated by cell viability assays using cultures of HeLa and Vero cell lines, and the mutagenic potential was assessed by the Ames test. In the broth microdilution test, compound 1 inhibited 90% of the strains tested at the minimum inhibitory concentration of 62.5 μg mL−1. Furthermore, both compounds prevented biofilm formation, with a reduction of up to 5.2 log10. HeLa and Vero cells exhibited 100% viability in the presence of compound 1. In contrast, low cell viability was observed in the presence of 15 µg mL−1 of compound 2. Furthermore, no mutagenic potential was detected at any of the tested concentrations of compound 1.